Pengaruh Kerjasama Tim Dan Knowledge Sharing Terhadap Kinerja Karyawan Pada PT. Santosa Utama Lestari Kabupaten Bima - Jumiati Jumiati; Kartin Aprianti (Jurnal Ekonomi, Bisnis dan Manajemen, 2023)
Developments in the business world are currently increasing rapidly, as seen from the many companies that have sprung up with various fields of development in the current business world. In carrying out its business activities, a company certainly requires various resources. Human resources are one of the resources that exist in a company in addition to other resources such as capital, materials and machines. Companies also need human resources, namely employees. Employees are an important resource for the company, because they have talent, energy and creativity that are needed to achieve company goals (Erwina & Mira, 2019).